2013
DOI: 10.3346/jkms.2013.28.11.1650
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Congenital Adrenal Insufficiency Including Growth Patterns and Significance of ACTH Stimulation Test

Abstract: Congenital adrenal insufficiency is caused by specific genetic mutations. Early suspicion and definite diagnosis are crucial because the disease can precipitate a life-threatening hypovolemic shock without prompt treatment. This study was designed to understand the clinical manifestations including growth patterns and to find the usefulness of ACTH stimulation test. Sixteen patients with confirmed genotyping were subdivided into three groups according to the genetic study results: congenital adrenal hyperplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Tieto poruchy môžu byť život ohrozujúce, ak sa včas neliečia. Pri neklasickej forme je u žien prítomný hirzutizmus s nadmernou tvorbou akné, menštruačné problémy, poruchy fertility u neliečených pacientiek, kým u mužov môže byť asymptomatickým ochorením s nejasným vplyvom na fertilitu [9]. Diagnostika CAH sa zakladá na klinickom zhodnotení, laboratórnych, zobrazovacích vyšetreniach a najmä genetickej analýze.…”
Section: úVodunclassified
“…Tieto poruchy môžu byť život ohrozujúce, ak sa včas neliečia. Pri neklasickej forme je u žien prítomný hirzutizmus s nadmernou tvorbou akné, menštruačné problémy, poruchy fertility u neliečených pacientiek, kým u mužov môže byť asymptomatickým ochorením s nejasným vplyvom na fertilitu [9]. Diagnostika CAH sa zakladá na klinickom zhodnotení, laboratórnych, zobrazovacích vyšetreniach a najmä genetickej analýze.…”
Section: úVodunclassified
“…3 The classical phenotypes are salt-wasting and simple genital virilizing forms. 5,6 In a study, conducted on 82 cases it was showed that consanguinity rate was high (71.2%), 95% had salt depletion and 52% had genital virilization. 7 One more study conducted on 28 cases showed that 60.7% cases had salt depletion and 39.3% had genital virilization.…”
Section: Introductionmentioning
confidence: 99%